PENGARUH PEMBERIAN EKSTRAK LADA HITAM (Piper nigrum L) TERHADAP LIBIDO (PERILAKU SEKSUAL) MODEL TIKUS PUTIH JANTAN (RATTUS NORVEGICUS) DIABETES MELITUS - Isvari, Gusti Ayu Made Prathita; Hadibrata, Exsa; Yunianto, Andi Eka; Susianti (CV. Jasa Sukses Abadi, 2024)
Abstract Diabetes Mellitus causes complications in the form of sexual libido dysfunction. Some of the treatment for libido dysfunction was aphrodisiac (piperin) which consist in black pepper. This study aimed to determine the effect of black pepper (piper nigrum l) extract on male white rat (Rattus norvegicus) libido (sexual behavior) with diabetes mellitus. The study was an experimental laboratory with a post-test only control group design using 30 samples of male white rats (Rattus norvegicus) which divided into 5 groups. Each divided into, control group 1 (K1) consist of normal rats; control group 2 (K2), diabetic rats induced by alloxan 150 mg/kg; treatment group 1 (P1), diabetic rats induced by alloxan 150 mg/kg and given black pepper extract 122.5 mg/kg; treatment group 2 (P2), diabetic rats induced by alloxan 150 mg/kg and given black pepper extract 245 mg/kg; treatment group 3 (P3), diabetic rats induced by alloxan 150mg/kg and given sildenafil 1mg/kg. Libido’s measurement was done by observing intromission latency in second, mount latency in second, mount frequency by its quantity. Kruskal-Wallis test was used to analyzed introducing latency, whereas mounting latency and mounting frequency was analyzed with One Way ANOVA. The results showed that introducing latency of group P1 and P2 significantly different compared to group K2 (p=0,003, p=0,003), Mounting latency of group P1 significantly different compared to group K2 (p=0,000) and mounting frequency of group P1 and P2 significantly different compared to group K2 (p=0,000,p=0,006). Black pepper extract enhances male white rat (Rattus norvegicus) libido with diabetes mellitus.